Activity-dependent gene transcription as a long-term influence on receptor signalling. (19th November 2009) - McDade, Donna M.; Conway, Ann-Marie; James, Allan B.; Morris, Brian J.
Abstract : The regulation of synaptic glutamate receptor and GABAA R (γ-aminobutyric acid subtype A receptor) levels is a key component of synaptic plasticity. Most forms of neuronal plasticity are associated with the induction of the transcription factor zif268 (egr1). Hence, it is predicted that zif268 may regulate transcription of genes associated with glutamate receptors and/or GABAA Rs. It turns out that receptor regulation by zif268 tends to be indirect. Induction of zif268 in neurons leads to altered expression of proteasome subunit and proteasome-regulatory genes, thereby changing the capacity of the neuron to degrade synaptic proteins, including receptors and receptor subunits. In addition, zif268 alters the transcription of genes associated with GABAA R expression and trafficking, such as ubiquilin and gephyrin. This indirect regulation of receptor turnover is likely to contribute to the delayed, but long-lasting, phases of synaptic plasticity and also to the synaptic dysfunction associated with diseases such as schizophrenia and Alzheimer's disease, where zif268 expression is reduced.